Customs tariff reform - Mukhopadhyay, Sukumar (2002)
Contrary to the claims of successive finance ministers, the Customs tariff remains highly complicated after more than a decade of supposed reforms since 1991. There are too many rates still, apart from some specific rates, innumerable exemptions, numerous conditions and lists. A reform agenda for the 2003-04 Budget. - Reproduced.
Keywords: Tariffs; Customs policy